UNIT 9.48 High Throughput‐Based Mitochondrial Function Assays by Multi‐Parametric Flow Cytometry. Issue 1 (1st July 2015) - Robinson, J. Paul; Li, Nianyu; Narayanan, Padma Kumar
Abstract : Mitochondrial dysfunction has been increasingly implicated as an important mechanism for chemical‐induced toxicity. In the present unit, we describe a multi‐parametric flow cytometry assay to assess the effects of drug or chemical‐induced mitochondrial dysfunction in cells. Cells are cultured in a glucose‐supplemented medium and exposed to increasing concentrations of various chemicals. Several key mitochondrial/cellular parameters known to be directly impacted by mitochondrial dysfunction, such as mitochondrial membrane potential (MMP), mitochondrial reactive oxygen species (ROS) production, intracellular reduced glutathione (GSH) level, and cell viability, are simultaneously measured by flow cytometry. © 2015 by John Wiley & Sons, Inc.